Record of mega-earthquakes in subduction thrusts: The black fault rocks of Pasagshak Point (Kodiak Island, Alaska) - Meneghini F.; Rowe, C. D.; Moore J. C.; Tsutsumi A.; Yamaguchi A.; DI TORO, GIULIO (Geological Society of America Bulletin, 2010)
On Kodiak Island, Alaska, decimeter-thick black fault rocks are at the core of foliated cataclasites that are tens of meters thick. The cataclasites belong to melange zones that are regarded as paleodecollements active at 12-14 km depth and 230-260 degrees C. Each black layer is mappable for tens of meters along strike. The black fault rocks feature a complex layering made at microscale by alternation of granular and crystalline micro textures, both composed of micronscale subrounded quartz and plagioclase in an ultrafine, phyllosilicate-rich matrix. In the crystalline microlayers, tabular zoned micro lites of plagioclase make up much of the matrix. No such feldspars have been found in the cataclasite. We interpret these crystalline microlayers as pseudotachylytes. The granular microlayers show higher grain-size variability, crushed microlites, and textures typical of fluidization and granular flow deformation. Crosscutting relationships between granular and crystalline microlayers include flow and intrusion structures and mutual brittle truncation. This suggests that each decimeters-thick composite black fault rock layer records multiple pulses of seismic slip. In each pulse, ultracomminuted fluidized material and friction melt formed and deformed together in a ductile fashion. Brittle truncation by another pulse occurred after solidification of the friction melt and the fluidized rock.